Using warm compresses to reduce IL-1β levels in dysmenorrhea: An evaluation of quasy experimental study - Mukhoirotin Mukhoirotin; Siti Urifah (Universitas Muhammadiyah Magelang, 2022)
Primary dysmenorrhea is a gynecological problem that occurs among adolescents and women of reproductive age. Theoretically, primary dysmenorrhea increases pro-inflammatory cytokine IL-1β levels. However, studies using warm compresses to reduce pain management in dysmenorrhea are limited. This study aimed to determine the effect of warm compresses to reduce IL-1β levels in primary dysmenorrhea. The research design used a quasi-experiment with a pretest-posttest study design. The population of this study was students experiencing dysmenorrhea. A total of 24 respondents was taken by using a simple random sampling technique. Hot water bags were the equipment for this study. The instrument for measuring pain used NRS (Numeric Rating Scale), and IL-1 β levels used the ELISA method. The data were analyzed by the Wilcoxon test and Mann-Whitney Test. The study showed there was a positive effect of warm compresses on dysmenorrhea (p ≤ 0.05). There were significant differences in the intensity of menstrual pain and IL-1β levels among the two groups of study (p ≤ 0.05). The recommendation for the next research should be focused on the different types of pain that commonly occur among women. Keywords: dysmenorrhea; pain management;pediatric nursing;nursing care; warm compresses